The Arabidopsis thaliana K+-Uptake Permease 5 (AtKUP5) Contains a Functional Cytosolic Adenylate Cyclase Essential for K+ Transport - Al-Younis, Inas; Wong, Aloysius; Lemtiri-Chlieh, Fouad; Schmöckel, Sandra; Tester, Mark; Gehring, Chris; Donaldson, Lara (Frontiers in Plant Science, 2018)
Potassium (K+) is the most abundant cation in plants, and its uptake and transport are key to growth, development and responses to the environment. Here, we report that Arabidopsis thaliana K+ uptake permease 5 (AtKUP5) contains an adenylate cyclase (AC) catalytic center embedded in its N-terminal cytosolic domain. The purified recombinant AC domain generates cAMP in vitro; and when expressed in Escherichia coli, increases cAMP levels in vivo. Both the AC domain and full length AtKUP5 rescue an AC-deficient E. coli mutant, cyaA, and together these data provide evidence that AtKUP5 functions as an AC. Furthermore, full length AtKUP5 complements the Saccharomyces cerevisiae K+ transport impaired mutant, trk1 trk2, demonstrating its function as a K+ transporter. Surprisingly, a point mutation in the AC center that impairs AC activity, also abolishes complementation of trk1 trk2, suggesting that a functional catalytic AC domain is essential for K+ uptake. AtKUP5-mediated K+ uptake is not affected by cAMP, the catalytic product of the AC, but, interestingly, causes cytosolic cAMP accumulation. These findings are consistent with a role for AtKUP5 as K+ flux sensor, where the flux-dependent cAMP increases modulate downstream components essential for K+ homeostasis, such as cyclic nucleotide gated channels.